2021
DOI: 10.1108/ilt-05-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Improved tribology performances of copper graphite (Cu/C) using a phosphorized oxidization surface obtained with tricresyl phosphate (TCP)

Abstract: Purpose Copper-graphite (Cu/C) is a type of seal material that has been widely used in liquid rocket engines and with normal metal pairs, has a high wear rate under liquid oxygen lubrication. In this study, bearing steel disks were subjected to a high-temperature oxidization and phosphating progress to create an oxidized tricresyl phosphating film (OTCP) film, using tricresyl phosphate (TCP) as the phosphating solvent. It is hoped that the surface wear rate and friction coefficient can be reduced by this metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Phosphating with a manganese composite solution provided the best corrosion resistance and wear resistance for gears. Lu et al (2021) found that bearing steel coated with an oxidized tricresyl phosphating (OTCP) film demonstrated improved tribological performance (lower COF and wear rate) when paired with Cu/C, outperforming both oxidized and untreated bearing steel. Additional chemical reactions occurred when the oxide disk was immersed in tricresyl phosphate, resulting in the formation of a FePO 4 film after heating.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphating with a manganese composite solution provided the best corrosion resistance and wear resistance for gears. Lu et al (2021) found that bearing steel coated with an oxidized tricresyl phosphating (OTCP) film demonstrated improved tribological performance (lower COF and wear rate) when paired with Cu/C, outperforming both oxidized and untreated bearing steel. Additional chemical reactions occurred when the oxide disk was immersed in tricresyl phosphate, resulting in the formation of a FePO 4 film after heating.…”
Section: Introductionmentioning
confidence: 99%